2022
DOI: 10.1136/bmjopen-2022-066359
|View full text |Cite
|
Sign up to set email alerts
|

‘Dynamic zero-COVID’ policy and viral clearance during an omicron wave in Tianjin, China: a city-wide retrospective observational study

Abstract: ObjectiveTo report how the Chinese mainland battled its first omicron wave, which happened in Tianjin, a metropolis with 14 million residents. We also sought to better understand how clinical features affected the timing of viral clearance.DesignA retrospective study of the omicron wave in Tianjin between 8 January 2022 and 3 March 2022.SettingExcept for the first cases on 8 January, all the omicron cases were identified through PCR mass testing in the residential communities. Residential quarantine and serial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…We have also shown that Omicron infection affects females more than males, with a ratio of 56.5% vs. 43.5%, respectively. This trend is consistent with the results of a previous study on the Omicron outbreak in Shanghai, which showed 54.7% for females and 45.3% for males ( 40 ). This may be due to the higher proportion of female medical staff, for example, women accounted for 56% of the medical staff assisting Hubei in Guangzhou, and they often play the role of caregivers and front-line healthcare workers in the family.…”
Section: Discussionsupporting
confidence: 93%
“…We have also shown that Omicron infection affects females more than males, with a ratio of 56.5% vs. 43.5%, respectively. This trend is consistent with the results of a previous study on the Omicron outbreak in Shanghai, which showed 54.7% for females and 45.3% for males ( 40 ). This may be due to the higher proportion of female medical staff, for example, women accounted for 56% of the medical staff assisting Hubei in Guangzhou, and they often play the role of caregivers and front-line healthcare workers in the family.…”
Section: Discussionsupporting
confidence: 93%
“…China has adopted a dynamic clearance strategy to stamp out SARS-CoV-2 outbreaks through implementation of control measures, such as stringent border control, meticulous quarantine, and mass screening ( 9 ). This strategy has been proven to be effective in containing the previous VOCs and maintaining an extended period of low level of SARS-CoV-2 cases ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The differences in HT were mainly between BA.2 and the other two variant strains, with the shortest HT in BF.7, whose median viral clearance interval was similar to 10 days in the Tianjin study in China [20]. By segmentation, we found that HT changes in the population's higher and lower age groups.…”
Section: Discussionmentioning
confidence: 57%